2009
DOI: 10.1002/jcp.21813
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DGK‐θ

Abstract: Diacylglycerol kinases are important regulators of lipid signaling and, consequently, important regulators of many diglyceride-dependent and PA-dependent proteins. Research over the last twenty years has clearly demonstrated that individual DGK isoforms can be connected with disparate cellular processes, indicating the presence of a sophisticated regulatory network for diglyceride and phosphatidic acid signaling through the regulation of individual DGK isoforms. This review presents the progress on the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…For example, the most commonly used DGKa inhibitors, R59949 and R59022, broadly attenuate other DGK isotypes, such as DGKe, DGKq, DGKg, DGKk, and DGKd (28). Thus, clinical application of such inhibitors would probably be associated with undesirable effects; it is known that mutations in some of the isotypes, such as DGKq and DGKd, cause neuronal defects (44,45). Lastly, systemic administration of DGK inhibitors would also pose significant safety concerns, given that systematic deficiency of DGKa and DGKz has been shown to significantly impair T-cell development in mice and that DGKz has been suggested to protect hippocampal neurons from ischemia (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the most commonly used DGKa inhibitors, R59949 and R59022, broadly attenuate other DGK isotypes, such as DGKe, DGKq, DGKg, DGKk, and DGKd (28). Thus, clinical application of such inhibitors would probably be associated with undesirable effects; it is known that mutations in some of the isotypes, such as DGKq and DGKd, cause neuronal defects (44,45). Lastly, systemic administration of DGK inhibitors would also pose significant safety concerns, given that systematic deficiency of DGKa and DGKz has been shown to significantly impair T-cell development in mice and that DGKz has been suggested to protect hippocampal neurons from ischemia (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…DGKγ, which is predominantly localized in Purkinje cells and hippocampus, is present at birth and then gradually increased [13,38]. The mRNA expression of DGKθ is the highest in cerebellum and hippocampus [18] and it is suggested that DGKθ is involved in neurotransmitter release [84]. However, further examination would be necessary to understand physiological functions of DGKα, γ, and θ in brain.…”
Section: Reviewmentioning
confidence: 99%
“…The optimal activation of DGKθ may require both polybasic protein and acidic phospholipid cofactors, which have been shown to stimulate DGKθ synergistically in vitro [25,26]. These multiple regulatory mechanisms enable DGKθ to mediate signals from a wide variety of extracellular ligands [24,27] including epidermal growth factor [28], nerve growth factor [29], α-thrombin [30], and adenosine [31]. …”
Section: Introductionmentioning
confidence: 99%